The effect of HIIT before and after hindlimb suspension on the gene expression of MSTN and ActrIIB in skeletal muscle of male Wistar rats - Maryam Afzali; Abdolreza Kazemi (فصلنامه ابن سینا)
Background and aims: Exercise training is employed as a practical method to combat muscle atrophy. The purpose of this study was to investigate the effects of high-intensity interval training (HIIT) conducted before and after hindlimb suspension (HLS) on the gene expression of MSTN and ActRIIB in the skeletal muscle of male Wistar rats. Methods: Thirty-two male rats, aged four to six months, were randomly divided into four groups (N=8 each): (1) control, (2) training-suspension-retraining, (3) non-training-suspension-retraining, and (4) training-suspension-non-training. The HIIT duration was five weeks, while the HLS lasted for two weeks. Gene expression levels were assessed using RT-PCR. Results: A significant decrease in the expression of MSTN and ActRIIB was observed in the soleus muscle of the group (2) compared to the other groups (p<0.05). There was also a notable reduction in MSTN expression in the extensor digitorum longus (EDL) muscle among the experimental groups relative to the control group (p<0.05), with the group (2) showing a greater effect than the others. Additionally, a significant decline in ActRIIB expression in the EDL muscle of the group (2) was noted compared to the other groups (p<0.05). The group (3) also exhibited a significant decrease in ActRIIB expression in the EDL muscle compared to the control group (p<0.05). Conclusion: The findings of this study suggest that the training-retraining approach (with HIIT) is particularly effective in mitigating muscle atrophy induced by HLS. These results highlight the HIIT training model as a highly efficient treatment method for preventing and reducing atrophy in rodent skeletal muscle.